Cytologic diagnostic approach of pleuropulmonary blastoma: a case report - Auliya Suluk Brilliant Sumpono; Alva Sinung Anindita; Junaedy Yunus; Didik Setyo Heriyanto (Universitas Gadjah Mada, 2022)
Pleuropulmonary blastoma (PPB) is a very rare pediatric lung tumor that arises in the pulmonary parenchyma, mediastinum, and pleura. The tumor has rapid disease progression and therefore the prognosis is remarkably poor. We reported a 4-year-old girl who complained of high fever and shortness of breath for the past 8 weeks. The patient was referred from the previous hospital with a pulmonary mass. CT scan of the chest with contrast showed a solid cystic mass with necrotic areas in the 1st, 2nd, and 3rd segments of the left lung with sized 4.8 x 8.1 x 6.6 cm3. As the tumor mass was inoperable, an ultrasound-guided fine-needle aspiration biopsy (FNAB) was conducted to diagnose the pulmonary lesion. We concluded that the lung tumor was a PPB based on FNAB cytology and immunocytochemistry staining. The histopathology feature of PPB appeared similar to fetal lung tissue. Cytologic features obtained from fine-needle aspiration cytology smears and cell blocks followed by immunocytochemistry assay could provide a proper and accurate diagnosis in an inoperable surgical pathology case.